Escherichia albertii Pathogenesis - Gomes, Tânia A T; Ooka, Tadasuke; Hernandes, Rodrigo T. [UNESP]; Yamamoto, Denise; Hayashi, Tetsuya (American Society for Microbiology, 2020)
Escherichia albertii is an emerging enteropathogen of humans and many avian species. This bacterium is a close relative of Escherichia coli and has been frequently misidentified as enteropathogenic or enterohemorrhagic E. coli due to their similarity in phenotypic and genetic features, such as various biochemical properties and the possession of a type III secretion system encoded by the locus of enterocyte effacement. This pathogen causes outbreaks of gastroenteritis, and some strains produce Shiga toxin. Although many genetic and phenotypic studies have been published and the genome sequences of more than 200 E. albertii strains are now available, the clinical significance of this species is not yet fully understood. The apparent zoonotic nature of the disease requires a deeper understanding of the transmission routes and mechanisms of E. albertii to develop effective measures to control its transmission and infection. Here, we review the current knowledge of the phylogenic relationship of E. albertii with other Escherichia species and the biochemical and genetic properties of E. albertii, with particular emphasis on the repertoire of virulence factors and the mechanisms of pathogenicity, and we hope this provides a basis for future studies of this important emerging enteropathogen.